Arsitektur Kolonial Modern Nieuwe Bouwen Di Kota Bandung Karya A.F. Aalbers (1931–1942) - Muhammad Gibran Humam Fadlurrahman (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This article examines the modern colonial architecture of Nieuwe Bouwen in Bandung through the works of Albert Frederik Aalbers from 1931 to 1942. A.F. Aalbers was a prominent architect in the Netherlands East Indies who contributed to the development of modern architecture through his works influenced by the international movement and Nieuwe Bouwen from Netherlands. He wass notable for his distinctive architectural style, which include the DENIS Bank, Savoy Homann Hotel, the renovation of Societeit Concordia, and villas such as De Locomotieven, De Driekleur, and Sadangsari. Bandung, one of the cities developed in colonial times, preserves many colonial buildings with diverse styles, providing evidence of the history of architectural development in Indonesia, and among them are Albers’ architectural works. His architectural works are significant in the history of Indonesian colonial architecture because his expressionist design, influenced by international architectural styles, were integrated into the urban planning of Netherlands East Indies. This research is a study of colonial architecture using historical methods consisting of heuristics, verification, interpretation, and historiography.